10-Year oncological outcome report after second conservative treatment for ipsilateral breast tumor event. (January 2023) - Hannoun-Levi, Jean-Michel; Gal, Jocelyn; Schiappa, Renaud; Chand, Marie-Eve
Highlights: Mastectomy is the historically standard treatment for ipsilateral breast tumor event. 10-y oncological results for 2nd conservative treatment confirmed the 5-y outcomes. APBI/molecular classifications and tumor size are prognostic factors. Second conservative treatment is a valuable alternative to salvage mastectomy. Abstract: Purpose: To analyze long-term oncological outcome after 2nd conservative treatment (2 nd CT) for patients with ipsilateral 2nd ipsilateral breast tumor event (2 nd IBTE). Materials/methods: In this retrospective observational study (N°F20210402152843), patients with 2 nd IBTE underwent 2 nd CT (lumpectomy + tumor bed re-irradiation). 3 rd IBTE (3 rd IBTE-FS), regional relapse- (RRFS) and metastatic disease- (MD-FS) free survivals as well as disease-free (DFS), specific (SS) and overall (OS) survival were analyzed. Late toxicity was reported. Results: Between 09/2000 and 04/2022, 244 patients presented a 2 nd IBTE and underwent a 2 nd CT. Among them, 113 pts with a minimum follow-up of 60 months were analyzed. Median time interval between 1st and 2 nd IBTE was 13.5 years [2–35]. Median 2 nd IBTE age was 66.2 years [31–85]. 2 nd IBTE were adenocarcinomas (77 %). Tumor size was < 20 mm (86.7 %). 2 nd IBTE were grade 1/2 (75 %), with positive hormonal receptor (85 %) and clear surgical margins (no ink on tumor, 90.3 %). In the APBI classification, 21 pts were high-risk (18.6 %), while 77 % were Luminal A/BHer2-. With a MFU of 121.5 months [CI95% 111.7–129.6], 10-year 3 rd IBTE-FS was 89 % [83–96]. Then-year RRFS, MDFS, DFS, SS and OS were 94 % [89–100], 89 % [83–96], 78 % [70–87], 95 % [91–100] and 94 % [90 –99] respectively. In multivariate analysis, APBI classification (high-risk; HR2.66 [1.01–7.1], p = 0.049) and tumor size (≥20 mm; HR2.64 [1.02–6.8], p = 0.045) were considered independent prognostic factors for DFS. Ninety-seven late complications were observed (fibrosis 64 %) with 6.2 % G ≥ 3 late toxicity. Cosmetic outcome was excellent/good in 91.2 %. Conclusions: With long follow-up, 2 nd IBTE managed with 2 nd CT allows second breast preservation without oncological outcome compromise and acceptable G ≥ 3 toxicity.